PCDDs and PCDFs in pelagic fish along the straits of Malacca - Mohamad Nasir, Nurul Nadiah; Azlan, Azrina; Razman, Muhammad Rizal; Ramli, Nor Azam; Abdul Latiff, Aishah (Universiti Putra Malaysia Press, 2012)
Fish and shellfish are rich sources of long chain fatty acids, especially DHA and EPA. High consumption of fish helps to elevate the level of these compounds in the body. However, fish also are easily exposed to chemical contaminants, such as dioxins (PCDDs) and furans (PCDFs). Exposure to PCDDs and PCDFs may lead to negative health effects, such as cancer, chloracne, hyperpigmentation and others. Level and type of PCDDs and PCDFs were determined in 20 pelagic fish samples of six different species collected from the Straits of Malacca using HRGC/HRMS. The most toxic congener (2,3,7,8-TCDD) was found in all the samples at a very low level of 0.04-0.05 pg/g sample, except in Spanish mackerel (south-T2) and Indian mackerel (middle-T1). Meanwhile, the level of the total PCDDs and PCDFs ranged from 0.13 pg/g to 0.38 pg/g of the wet weight of the samples. The value of the total PCDDs and PCDFs was in a descending order of Hardtail scad, Spanish mackerel, Indian mackerel, fourfinger threadfin, silver pomfret and dorab wolfherring. Generally, the results of this study indicate that fish and shellfish caught along the Straits of Malacca are safe as in terms of PCDDs and PCDFs levels and the data can serve as baseline information for future monitoring of these organochlorine compounds.